Enhancing mHealth data collection applications with sensing capabilities - Karthan, Maximilian; Martin, Robin; Holl, Felix; Swoboda, Walter; Kestler, Hans A.; Pryss, Rüdiger; Schobel, Johannes (Frontiers in Public Health, 2022)
Smart mobile devices like smartphones or tablets have become a salient factor for collecting data in complex healthcare scenarios (i.e., psychological studies, medical trials), slowly replacing traditional pen-and-paper instruments. However, by simply digitizing such instruments, the full potential of such devices is not fully utilized yet: Most modern devices comprise a variety of different sensing capabilities (i.e., microphone, GPS data, camera, ...), which may also provide valuable data and potentially valuable insights for healthcare professionals and researchers. Considerable development effort is required to integrate sensing capabilities into (existing) data collection applications. Developers may have to deal with platform-specific peculiarities (i.e., Android vs. iOS) or proprietary sensor data formats, which lead to unnecessary development overhead when supporting researchers with such digital solutions. A cross-platform mobile sensing framework has been developed to enhance existing data collection applications with sensing capabilities to cope with these issues. This framework will allow researchers to collect additional information from participants as well as their environment, increasing the amount of data that is collected and potential new insights from existing data.